Compendium of Evaluation Studies Conducted by Programme Evaluation Organisation (1983-99) Volume-III - Planning Commission (Planning Commission, 1999)
Evaluation is an integral part of planning process. Plan Schemes are formulated and implemented without adequate knowledge of the project area, target groups, grass root level institutions and about the likely behaviour of implementators and beneficiaries. Feedback from monitoring and evaluation is, therefore, an important tool to assess the appropriateness of design and implementation methods and take the necessary corrective measures for improving the performance. Keeping in view the importance of such an efficient evaluation system, the Programme Evaluation Organisation (PEO) was set up in the Planning Commission, Government of India, as early as 1952 with the avowed objective of evaluating the Community Development Programme which was launched during the First Five Year Plan period.
Government of India Planning Commission Programme Evaluation Organisation